Determination of genetic diversity of rhododendron species in Turkey - Kaya, İsmail Tuğberk. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
The Rhododendrons of Turkey are presented by 10 taxa and they grow naturally along the coast of the Black Sea region from Artvin province at the east to Istranca Mountains at the west. Although in many countries, cultivated natural forms or breeding varieties of Rhododendron genus are highly used in landscape planning and as ornamentals, in Turkey there are no cultivated local forms available and all commercial varieties are imported as potted plants. Recently, a national project has started with an objective to generate well documented ex-situ conservation of all naturally growing Rhododendron species of Turkey following a detailed morphological, molecular studies and tissue culture propagations. As partners of this project our aim is to analyze the genetic diversity by incorporating possible impacts of location and altitude to their diversity. The plant material has been collected from nature at di erent GPS locations and diverse altitudes along the cost of Black Sea and Marmara region. Total of 22 primers consisting of RAPD, ISSR and ITS markers were selected to study the genetic diversity and phylogenetic relationship among the samples. Genetic distance calculations of the data matrix to generate cluster analysis were performed by UPGMA using Pearson and Jaccard coe cient. The dendograms re ecting the genetic distance were drawn using MATLAB. All primers have shown 100% polymorphism, producing amplicons ranging between 200-3000bp. The average number of bands obtained for ISSR and RAPD primers were 19.1 and 20.9 respectively. The impact of geographic range on the species genetic diversity were clearly observed in cluster analysis when highly wide spread wild species were clustered as separate groups from the other wild species which has very narrow range of natural growth locations.
Keywords: Rhododendrons -- Turkey.